Proton conducting perovskite hollow fibre membranes with surface catalytic modification for enhanced hydrogen separation - Song, J.; Kang, J.; Tan, X.; Meng, B.; Liu, Shaomin (2015)
BaCe0.85Tb0.05Co0.10O3-d (BCTCo) perovskite hollow fibre membranes were fabricated by a combined phase-inversion and sintering technique. The hollow fibre surfaces were modified by coating Ni or Pd particles. Hydrogen permeation fluxes at 700-1000°C can be improved due to the surface modification from the original 0.009-0.164mL(STP) cm-2 min-1 to 0.018-0.269mLcm-2 min-1 for the Ni-coated membranes with maximum improvement by 64%, and to 0.1-0.42mLcm-2 min-1 for the Pd-loaded membranes with maximum enhancement by 155%, respectively. Loading of the catalyst on the hollow fibre outer surface is better than on the inner surface, but coating on both sides may enhance the hydrogen permeation most effectively. The permeation enhancement depends on both the catalyst loading amount and its structure, which can be controlled by the plating conditions. The optimal Pd loading and coverage should be around 0.667mgcm-2 and 82%, respectively for maximizing the permeation improvement.